Ocean fracture zones: their evolution and impact on tectonic and magmatism of the South and Southeast Brazilian continental margin - Alves, Eliane C.; Araujo, Rogério S.; Ramos, Edmarley C.; Maia, Márcia; Santos, Anderson Costa dos; Hackspacher, Peter Christian [UNESP] (Elsevier, 2021)
Consideration of Mesozoic-Cenozoic tectonic and magmatic activities of the South and Southeast Brazilian continental margin shows that fracture zones (FZs) had a fundamental role in the forming the South Atlantic during the formation of the oceanic plate between the early Cretaceous and Cenozoic. FZs have the most significant morphotectonic and magmatic characteristics, identified from north to south as the Santa Helena FZ, Vitória Trindade FZ, Martin Vaz FZ, Rio de Janeiro FZ, and Rio Grande FZ. We compiled a set of geological and geophysical data, including bathymetry, gravimetry (free air, vertical gravity gradient, and geoidal), and magnetometry (magnetic and isochronous anomalies), associated with the reflection seismic from the Mid-Atlantic Ridge (its transforming characteristics) and its extensions in oceanic and continental crusts. This integration allowed an elaboration of hypotheses about the influence of mechanisms in the oceanic and continental crusts, and the influence on tectonic and magmatic segmentation in the continental margin and on the adjacent continental border beyond breakup spreading from south to north in three stages: (1) 122-125Ma, (2) 125-118Ma, and (3) 118-116Ma, physically separated by oceanic FZs. The width of the stretched and strongly intruded continental crust also showed an increase in three stages in the same direction and the same FZ. Consequently, the Continental-Oceanic Boundary showed three stages of marked changes from west to east and from south to north, resulting in margin segmentation. Rifting also spread from west to east, toward the final division, in each of these three defined segments.
Keywords: Brazilian offshore evolution; Earth surface processes; Fracture zones; Geophysics; Time period